(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
The central objective of this article is to reflect on the possibilities an anti-racist education in performing arts classes. Thus, we presented two pedagogical practices developed in basic education that used literature and role-playing games to discuss Blackness, Whiteness, and representation with children aged 9 to 11 from two different social classes. To this end, we employed action research methodological approaches. The study data demonstrated the importance of theater classes as a potentializer of dialogue across differences and how the actions developed could contribute to transformative education.